The Effect of E-WOM on Green Purchase Behavior - Ratih Pandu Mustikasari (Arkus, 2023)
E-Wom, as a form of marketing communication, makes many contributions to marketing activities. E-Wom, in several previous studies, showed a contribution to consumer behavior. This study links the concept of E-Wom with green products and looks at its effect on Green Purchase Behavior. Green product is currently a much-discussed issue, given the increasingly felt impact of global warming. Global warming has finally forced corporates and consumers to be wise in choosing products. The method used in this research is an explanatory quantitative method, with a data collection tool in the form of a questionnaire. Respondents in this study were late adolescents and early adults in Surabaya and its surroundings. The results of this study indicate that E-Wom about green products has a significant influence on green purchase behavior. The influence of E-Wom as a single factor is not that strong. Another finding recorded in this study is the high value of the share information product that occurs. Most of the respondents were reluctant to start a chat about product reviews, they would provide arguments if they had started, and the E-Wom in this study was more on a personal level.